Effect of postproduction heating on the texture properties of a standard sausage that contains a chicken paste meat extender (2015)
The objective of this study was to evaluate the textureproperties of a standard sausage that contained a chicken meatextender at a replacement percentage of 35% of the PMD whensubjected to postproduction heating. An experimental designthat looked at the combination of three extenders in ten mixturepoints was used; the extenders were composed of fiber, pig skin,and carrageenan, respectively, and there was one product withoutan extender. Five days after production, the sausages were cookedfor two hours at 80°C. An instrumental texture analysis and afirmness and elasticity evaluation were carried out on the recentlyproduced samples and on samples after the subsequent thermaltreatments. Hardness, masticability and firmness decreased withthe application of the thermal treatments. In addition, a synergisticinteraction was seen between the fiber and the carrageenan at thetwo temperature levels. It was concluded that the fiber, the pig skinand the carrageenan did not exhibit properties that were similarto those of chicken paste because their applications demonstrateda marked decrease in the texture properties, a decrease thatwas more pronounced when the product was subjected topostproduction heating.